“La Acción Pauliana y su incidencia en la rescisión de los contratos de compraventa en la Unidad Judicial de lo Civil del cantón Riobamba en los años enero 2015 – julio 2016.” - Rodríguez Gallegos, Gabriela Elizabeth (2017)
The present work research is refers to the rights of the creditor in enforced execution, to achieve compliance in some contracts also provides for compensation for damages caused in case of non-compliance. From this understanding, the doctrine has stipulated auxiliary rights that are added to certain contracts to ensure compliance, such is the case of the loan in any form, since obligation to give in channeled as a payment obligation. One of these auxiliary under article 2367 of the Civil Code is the general right of pledge, which is that the creditor is entitled over all assets of the debtor in case of breach of this obligation, so that these assets are constituted as a source of the repayment of the obligation, this rule is of importance to the debtor to keep his assets and not dispose of them. The purpose of the present investigation is to analyze the possibility that the debtor who has fallen into arrears may distract his assets by fraudulently selling them to another person in order not to fulfill his obligation to pay. For which Civil Law has created he Pauliana Action or Revocatory, this is an action that is granted to the creditor, to revoke the acts executed by the debtor in fraud to conceal his assets, to prevent these are seized and capped. Consequently, this investigation first addresses the Pauline action, in addition to the effects it generates, to determinate whether the Pauline action is an effective means to rescind the contract fraudulent.